2016
DOI: 10.1007/s10842-016-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

A Stochastic Production Frontier Estimator of the Degree of Oligopsony Power in the U.S. Cattle Industry

Abstract: The objective of this study is to estimate the degree of oligopsony power in the U.S. cattle industry with the use of the recently developed stochastic frontier estimator of market power. Unlike the seminal paper where estimation of the mark-up in an output market at firm level was the main objective, this work proposes a stochastic production frontier estimator in order to estimate the mark-down in an input market at aggregate level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…For example, the share of farmers using contracts with processors in the pig meat sector ranges from about 10% in Germany and Ireland to more than 70% in Finland and more than 80% in Spain (Fischer et al, 2009[61]). The literature shows clear efficiency benefits from the use of contracts (Otsuka, Nakano and Takahashi, 2016 [62]); nevertheless, concerns have been voiced around the possibility that farmers could be "locked in" to a relationship (and could then become vulnerable to unfair trading practices, as discussed in the previous section), as well as the possibility that some farmers will be "locked out"unable to contract with any processor and therefore unable to find a market for their products (Sexton and Xia, 2018[16]). 35 Quality concerns are an important cause of the growing use of contracts.…”
Section: Market Power Bargaining Power and Food Chain Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…For example, the share of farmers using contracts with processors in the pig meat sector ranges from about 10% in Germany and Ireland to more than 70% in Finland and more than 80% in Spain (Fischer et al, 2009[61]). The literature shows clear efficiency benefits from the use of contracts (Otsuka, Nakano and Takahashi, 2016 [62]); nevertheless, concerns have been voiced around the possibility that farmers could be "locked in" to a relationship (and could then become vulnerable to unfair trading practices, as discussed in the previous section), as well as the possibility that some farmers will be "locked out"unable to contract with any processor and therefore unable to find a market for their products (Sexton and Xia, 2018[16]). 35 Quality concerns are an important cause of the growing use of contracts.…”
Section: Market Power Bargaining Power and Food Chain Architecturementioning
confidence: 99%
“…Another study investigated contracts and price formation in fruit markets. 62 The report notes that fruit producers have a weak bargaining position; and UOKiK has conducted several investigations into violations of the 2016 law on unfair use of superior bargaining power. In addition, the UOKiK study identified various unfair trading practices, such as lengthy payment terms (of up to 180 days), failure to pay, and unclear pricing rules.…”
Section: Polandmentioning
confidence: 99%
See 1 more Smart Citation
“…Morrison (2001) estimates the beef packing industry in the U.S., where slight market power is exploitable in the cattle input or beef output markets [19]. Panagiotou and Stavrakoudis (2017) estimate that the degree of market power in the U.S. beef packing industry was 3.74% by using a stochastic frontier estimator [20]. Ji, Chung, and Lee (2017) estimate the existence of oligopsony power in the U.S. cattle market.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of market power is highly correlated to policy study. There are many articles estimating the market power effects of the Livestock Mandatory Reporting Act (LMRA) in the U.S. beef industry [20,[31][32][33]. These prove that the market power exertion of fed cattle markets was greater in the years after the program was implemented than before.…”
Section: Introductionmentioning
confidence: 99%